Publicly Involved Spatial Development in the Podkarpackie Voivodship in Poland from an Environmental Point of View - Małgorzata Roge-Wiśniewska (Barometr Regionalny, 2015)
The paper focuses on methods used during public consultations on conditions and directions of local spatial development prepared by communes (Polish: gmina) in the Podkarpackie Voivodship. A well-executed public communication process should provide information on public preferences and concerns, as well as additional environmental information. This research has proven a hypothesis that communication techniques used by communes during studies on the conditions and directions of local spatial development differ between communes with environmentally valuable areas and those without areas of special natural value.